Prevalence of Subclinical Mastitis, Associated Risk Factors and Pathogens in Dairy Cattle of West Coastal India - Rajkumar, Susitha; M, Anandhi; Nayakvadi, Shivasharanappa; Narnaware, Shirish D; Racharla, Solomon Rajkumar; Vithalrao, Udharwar Sanjay Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Mastitis is one of the most expensive diseases of dairy animals and subclinical mastitis occupies the major proportion of mastitis.  Prevalence of mastitis is highly dependent upon type of breed, climatic and housing conditions, management practices, stage of  lactation, etc. and hence a study was conducted to screen the prevalence of subclinical mastitis (SCM), associated risk factors, and  prevalent pathogens in small backyard and large organized dairy units in four districts in the west coast of India. A total of 240 cattle  were screened for subclinical mastitis and milk samples from SCM cases were screened for the presence of major mastitis-associated  pathogens. Information on managemental practices was collected and risk factors were analyzed statistically. The prevalence of clinical  and subclinical mastitis was 9.93% (27/272) and 30.83% (74/240), respectively. Staphylococcus aureus, coagulase-negative Staphylococci,  E coli, and Bacillus spp. were the major pathogens isolated from SCM cases. The study revealed that SCM is highly prevalent in dairy  farms of coastal districts and higher in crossbred than the indigenous cattle. The absence of regular shed cleaning and the use of milking  machines were significantly associated with higher SCM prevalence. Post-milking iodine teat dip was carried out by 27.5% and 88.89%  of the small and large farmers and none of the farmers had adopted dry cow therapy. Around 10.0% of small farmers and 77.78% of the  large farmers used milking machines. The high prevalence of SCM shows the need for active surveillance programs and the application  of preventive measures in the area.
Keywords: Cattle; Subclinical mastitis; Risk factors; mastitis pathogens; West coastal India